Humor at Work Questionnaire - Polish adaptation of Humor Climate Questionnaire (HCQ) - Aleksander Stańczak; Marcin Drabek (Nofer Institute of Occupational Medicine, 2018)
Background The aim of the paper is to present the Polish adaptation of the Humor Climate Questionnaire (HCQ), designed to measure humor as organizational climate feature. Material and Methods The authors employed back-translation and independent judges method to choose the best version of the translated items. The psychometric properties of HCQ were estimated on the basis of 2 samples: the basic group of employees (N = 217) and the group of employees who had completed the survey twice (N = 55). Results The results of statistical analyses proved that HCQ is a reliable tool. Explorative Factor Analysis supported the 4-factor structure of the original method's theoretical model. The validity of the subscales is high, Cronbach's α varied from 0.8 to 0.9. The directions and values of intercorrelations between subscales were similar to those of the English version. The Humor Climate Questionnaire is a relatively time-stable tool (r = 0.44-0.74). Conclusions Polish adaptation is reliable and applicable for cross-sectional studies. The obtained results are comparable to the characteristics of the original version. However, the results of factor analysis show that the data do not fully fit the theoretical model. Med Pr 2018;69(2):143-152